SOME SOURCES ON MUSLIM CHEMISTRY AND MEDICINE DURING THE EASTERN RENAISSANCE AND THEIR EARLY TRANSLATIONS - Abdurahimov Javlonbek son of Bahodirjon (Web of Journals Publishing, 2024)
In this article, some sources related to the chemistry and medicine of the Muslim East in the Middle Ages and which are now considered the most important in these areas are researched. In particular, Ibn an-Nadim's "Kitab al-Fihrist al-'ulum" ("The Book of the Bibliography of Sciences"), "Tarikh al-Baghdad" ("History of Baghdad") by Al-Khatib al-Baghdadi ), Ibn al-Qifti's "Ikhbar al-ʿulamoʾ bi akhbar al-hukamo" ("The Book of Acquainting Scholars with Information About Judges"), "ʿUyun al-Anbaʾ fi Tabaqat al-Atibbo" ("The Categories of Doctors" by Ibn al-Usaybi'a some comments about his works named "main messages about".
Keywords: Jabir ibn Hayyan, Abu Ali ibn Sina, Abu Bakr al-Razi, chemistry, medicine, Ibn an-Nadim, Central Asia, Eastern Renaissance.